New CPC Regulation and ECN+ Directive: the powers of national authorities in the fields of consumer protection and antitrust - Claudia Massa (Market and Competition Law Review)
National authorities in individual countries are responsible for the enforcement of EU consumer protection and antitrust laws together with the European Commission. This article seeks to define the powers of national consumer and antitrust authorities when enforcing those laws. In doing so, it analyses two main EU acts: on the one hand, EU Regulation no. 2017/2394, thanks to which national consumer authorities now have stronger powers to detect irregularities and take speed action; on the other hand, EU Directive 2019/1 that aims to ensure that, when applying the EU antitrust rules, national competition authorities have the appropriate enforcement tools in order to bring about a genuine common competition enforcement area. The article will also take into consideration that in both the consumer protection and the antitrust fields, the national authorities act in the framework of Networks (the “Consumer Protection Cooperation Network” and the “European Competition Network”), and it will emerge that this aspect also helps to define the scope of the action and inter-action of those authorities. In fact, the exercise of their powers must always take place in compliance with and within the limits imposed by the EU law principle of sincere cooperation enshrined by Article 4(3) TEU.